Parahaemophilia: A Rare Case Report (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Parahaemophilia or Owren’s diseaseis a rare haemorrhagic disorder occurs due to congenital and frequently familial deficiency of Factor V.It is characterized by epistaxis, bruising, mucosal bleeding, soft tissue bleeding and haemarthrosis. We report a case of 6 year old female patient with overlapping features with other haemorrhagic disorder. With the complaints of recurrent episodic per rectal bleeding, patient was evaluated at different hospitals in Chattagram and was diagnosed as a case of Haemophilia B and treated accordingly. As her condition was not improved expectedly, she was referred to Armed Forces Institute of Pathology (AFIP) for further evaluation. The lab tests showed prolongation of prothrombin time (PT) and activated partial thromboplastin time (APTT), with normal bleeding time (BT) and thrombin time (TT). Coagulation factors assay revealed a significant decrease of factor V, 1% of normal range. Other coagulation factors are normal. She was treated with FFP and recovered four weeks after treatment.J Bangladesh Coll Phys Surg 2020; 38(4): 205-208